Associations between smoking and caffeine consumption in two European cohorts. - Treur, Jorien L.; Taylor, Amy E.; Ware, Jennifer J.; McMahon, George; Hottenga, Jouke‐Jan; Baselmans, Bart M. L.; Willemsen, Gonneke; Boomsma, Dorret I.; Munafò, Marcus R.; Vink, Jacqueline M. (Addiction, 2016)
Aims To estimate associations between smoking initiation, smoking persistence and smoking heaviness and caffeine consumption in two population-based samples from the Netherlands and the United Kingdom. Design Observational study employing data on self-reported smoking behaviour and caffeine consumption. Setting Adults from the general population in the Netherlands and the United Kingdom. Participants Participants from the Netherlands Twin Register [NTR: n = 21 939, mean age 40.8, standard deviation (SD) = 16.9, 62.6% female] and the Avon Longitudinal Study of Parents and Children (ALSPAC: n = 9086, mean age 33.2, SD = 4.7, 100% female). Measurements Smoking initiation (ever versus never smoking), smoking persistence (current versus former smoking), smoking heaviness (number of cigarettes smoked) and caffeine consumption in mg per day through coffee, tea, cola and energy drinks. Findings After correction for age, gender (NTR), education and social class (ALSPAC), smoking initiation was associated with consuming on average 52.8 [95% confidence interval (CI) = 45.6-60.0; NTR] and 59.5 (95% CI = 51.8-67.2; ALSPAC) mg more caffeine per day. Smoking persistence was also associated with consuming more caffeine [+57.9 (95% CI = 45.2-70.5) and +83.2 (95% CI = 70.2-96.3) mg, respectively]. Each additional cigarette smoked per day was associated with 3.7 (95% CI = 1.9-5.5; NTR) and 8.4 (95% CI = 6.9-10.0; ALSPAC) mg higher daily caffeine consumption in current smokers. Smoking was associated positively with coffee consumption and less strongly with cola and energy drinks. For tea, associations were positive in ALSPAC and negative in NTR. Conclusions There appears to be a positive association between smoking and caffeine consumption in the Netherlands and the United Kingdom.